2006
DOI: 10.1073/pnas.0603391103
|View full text |Cite
|
Sign up to set email alerts
|

Apicoplast fatty acid synthesis is essential for organelle biogenesis and parasite survival inToxoplasma gondii

Abstract: Apicomplexan parasites are the cause of numerous important human diseases including malaria and AIDS-associated opportunistic infections. Drug treatment for these diseases is not satisfactory and is threatened by resistance. The discovery of the apicoplast, a chloroplast-like organelle, presents drug targets unique to these parasites. The apicoplast-localized fatty acid synthesis (FAS II) pathway, a metabolic process fundamentally divergent from the analogous FAS I pathway in humans, represents one such target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
256
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(277 citation statements)
references
References 46 publications
18
256
0
2
Order By: Relevance
“…Since acyl lipid labeling is abolished by treatment with haloxyfop, a reported inhibitor of the apicoplast acetyl CoA carboxylase, Bisanz et al (13) concluded that an active FAS II was critical for the bulk of the acyl lipid synthesis. Combining conditional mutant analyses and metabolic labeling, Mazumdar et al (5) demonstrated that FAS II was critical for the biogenesis of the apicoplast itself, and subsequently for parasite survival, but was unlikely the source of the acyl moiety of the bulk of acyl lipids. Rather, most glycerolipids from free T. gondii cells appears to be produced using acyl chains generated by FAS I or FAEs, which are resistant to the FAS II inhibitor thiolactomycin, but sensitive to the general FAS inhibitor cerulenin (5).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Since acyl lipid labeling is abolished by treatment with haloxyfop, a reported inhibitor of the apicoplast acetyl CoA carboxylase, Bisanz et al (13) concluded that an active FAS II was critical for the bulk of the acyl lipid synthesis. Combining conditional mutant analyses and metabolic labeling, Mazumdar et al (5) demonstrated that FAS II was critical for the biogenesis of the apicoplast itself, and subsequently for parasite survival, but was unlikely the source of the acyl moiety of the bulk of acyl lipids. Rather, most glycerolipids from free T. gondii cells appears to be produced using acyl chains generated by FAS I or FAEs, which are resistant to the FAS II inhibitor thiolactomycin, but sensitive to the general FAS inhibitor cerulenin (5).…”
mentioning
confidence: 99%
“…Combining conditional mutant analyses and metabolic labeling, Mazumdar et al (5) demonstrated that FAS II was critical for the biogenesis of the apicoplast itself, and subsequently for parasite survival, but was unlikely the source of the acyl moiety of the bulk of acyl lipids. Rather, most glycerolipids from free T. gondii cells appears to be produced using acyl chains generated by FAS I or FAEs, which are resistant to the FAS II inhibitor thiolactomycin, but sensitive to the general FAS inhibitor cerulenin (5). Together, these analyses highlight the importance [1] of the parasite FAS for bulk acyl lipid syntheses in free stages and [2] of the FAS II activity for the apicoplast biogenesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The obvious advantage of this strategy is that hypothetical genes that might otherwise be neglected in targeted approaches will be identified with equal probability. The Tet-inducible transactivator system is currently the most robust method to generate conditional mutants for essential genes in a targeted approach and appears to be especially well suited for the characterisation of factors involved in invasion and apicoplast biology (Meissner et al 2002, Mital et al 2005, Huynh & Carruthers 2006, Mazumdar et al 2006, Kessler et al 2008, Plattner et al 2008) whereas employment of the system for other essential GOIs might result only in weak phenotypes (Fleige et al 2008) or might not be possible at all (unpublished observations). A major advantage of the Tet-inducible system is that virtually any GOI can be regulated whereas regulation at the protein level using ddFKBP might not work for proteins targeted to the secretory system (Herm-Gotz et al 2007, and unpublished observations).…”
Section: Molecular Tools For Identification and Characterisation Of Ementioning
confidence: 99%